Discussion (Scottish Historical and Archaeological Internet Reports, 2005)
The debitage, core and tool distribution are discussed, as well as the activities suggested by the scattering of artefacts. First the internal distribution pattern of the three houses is dealt with, followed by the distribution across the three houses. As the principles of recovery and recording of finds differ from house to house, and between layers, the author was incapable of producing standardised distribution maps. The assemblage appears homogenous, typologically and well as technologically. It includes few strictly diagnostic elements, but two leaf-shaped arrowheads suggest an early Neolithic date. The assemblage is compared with other Neolithic quartz and non-quartz assemblages from Scotland, but only finds from settlements are included in the comparison.